Anaesthetic effects of sodium bicarbonate on red tilapia juvenile fish (Oreochromis spp.) - Chen, Hui Cheng; Mohamad Tahir, Nur Diyana; Abu Hamid, Muhammad Hanif (Malaysian Veterinary Medical Association, 2024)
Red tilapia fish (Oreochromis spp.) is one of the major species in the aquaculture industry in Malaysia. Sodium bicarbonate is widely available, and has been suggested as potential to anaesthetise fish safely. This study evaluates the potential of sodium bicarbonate immersion to induce anaesthesia in red tilapia juvenile fish. A total of 40 fish were randomly assigned into four groups. The four treatment groups were 25 g/L, 50 g/L, and 75 g/L sodium bicarbonate, and 150 ppm tricaine methanesulfonate (MS-222). Fish were recovered once attained surgical (Stage IV) anaesthesia, or 15 minutes of immersion, whichever earlier. Fish in 25 g/L and 50 g/L sodium bicarbonate achieved only light anaesthesia (Stage III) within the 15 minutes. Fish in 75 g/L sodium bicarbonate and MS-222 reached surgical anaesthesia at 195 ± 88 and 418 ± 74 seconds, respectively. All 40 fish regained normal swimming patterns within 10 minutes of recovery. However, all fish exposed to sodium bicarbonate died within 2 days post-recovery, while all fish in MS-222 survived. Results suggest sodium bicarbonate can induce light to surgical anaesthesia. However, the 100% mortality post-recovery from sodium bicarbonate raises safety concern on its use in red tilapia juvenile fish.